Barrier film, and wavelength conversion sheet, backlight, and liquid crystal display device using the same

CN116490808BActive Publication Date: 2026-10-27DAI NIPPON PRINTING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180069611.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-19
Filing Date
2021-08-03
Publication Date
2026-10-27
Estimated Expiration
2041-08-03

AI Technical Summary

Technical Problem

[0010]量子点具备上述优异的特征,但另一方面存在容易因水分、氧等的影响而劣化的问题

Benefits of technology

[0035]本发明的阻隔膜、以及使用了该阻隔膜的波长转换片、背光源和液晶显示装置能够抑制色调的变化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116490808B_ABST
    Figure CN116490808B_ABST
Patent Text Reader

Abstract

A barrier film is provided that can suppress hue changes when applied to a wavelength conversion film. The barrier film for a wavelength conversion film has, sequentially, an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a base layer D on a light-transmitting substrate. The thicknesses of the light-transmitting substrate, the inorganic oxide layer A, the organic coating layer B, the inorganic oxide layer C, and the base layer D are defined as t0, t1, t2, t3, t4, t5, t6, t7, t8, t9, t1, t1, t2, t1, t2, t3, t4, t5, t1, t2, t3, t4, t5, t6, t7, t8, t9, t1, t1, t2, t1, t2, t3 ...3, t4, t2, t3, t3, t4, t3, t2, t3, t3, t4, t3, t3, t3, t4, t3, t3, t3, t3, t3, t3, t3, t3, t3, t3, t3, t3 A t B t C and t D At that time, t B For wavelengths between 150nm and 500nm, and t D / t B It is between 0.55 and 1.65.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a barrier film, as well as a wavelength conversion sheet, a backlight, and a liquid crystal display device using the barrier film. Background Technology

[0002] With the development of personal computers, such as portable PCs, the demand for LCD display devices is increasing. Furthermore, the penetration rate of LCD TVs in homes is also rising recently, and smartphones and tablets are becoming increasingly widespread. Therefore, the market for LCD display devices is expanding rapidly.

[0003] Such liquid crystal display devices typically include a color filter, liquid crystal cells, and a backlight. Furthermore, liquid crystal display devices usually utilize the shutter function of the liquid crystal layer within the liquid crystal cells to control the intensity of light, and use color filters to separate the colors of each pixel into the three primary colors R, G, and B to represent the image.

[0004] Cold cathode tubes (CCTVs) have traditionally been used as the backlight source for liquid crystal display devices. However, in terms of low power consumption and small space requirements, LEDs have been replaced with CTVs as the backlight source.

[0005] The LEDs used as typical backlight sources are white LEDs, which are combinations of blue LEDs and YAG-based yellow phosphors. These white LEDs have a broad spectral distribution of emission wavelengths and are therefore referred to as pseudo-white.

[0006] On the other hand, the development of backlights using quantum dot technology has also been progressing in recent years. Quantum dots are nano-sized particles of semiconductors.

[0007] The basic structure of a backlight using quantum dots is a combination of a light source that produces primary light (such as a blue LED that emits blue light) and quantum dots.

[0008] Quantum dots can be categorized as semiconductor microparticles consisting of a CdSe core and a ZnS shell, or nanoscale compound semiconductor microparticles consisting of ligands covering the periphery of the shell. Because their particle size is smaller than the Bohr radius of the excitons in compound semiconductors, quantum dots exhibit a quantum confinement effect. Therefore, quantum dots demonstrate higher luminescence efficiency than conventional phosphors using rare-earth ions as activators, achieving luminescence efficiencies exceeding 90%.

[0009] Furthermore, the emission wavelength of quantum dots is determined by the band gap energy of such quantized compound semiconductor particles, so any emission spectrum can be obtained by changing the particle size of the quantum dots. Backlights that combine these quantum dots with blue LEDs can achieve high color purity with high luminous efficiency (see, for example, Patent Documents 1-2).

[0010] Quantum dots possess the aforementioned excellent characteristics, but they are also susceptible to degradation due to factors such as moisture and oxygen. Therefore, it is preferable to protect the two sides of the quantum dot layer using a barrier film.

[0011] Patent documents 3 and 4 propose a wavelength conversion sheet that uses a barrier film having a substrate, an inorganic oxide layer, and an organic coating layer to protect the quantum dot containing layer.

[0012] Existing technical documents

[0013] Patent documents

[0014] Patent Document 1: International Publication No. 2012 / 132239

[0015] Patent Document 2: Japanese Patent Application Publication No. 2015-18131

[0016] Patent Document 3: Japanese Patent Application Publication No. 2019-126924

[0017] Patent Document 4: Japanese Patent Application Publication No. 2020-19141 Summary of the Invention

[0018] The problem that the invention aims to solve

[0019] However, liquid crystal display devices using the wavelength conversion sheets of Patent Documents 3 and 4 often exhibit images with different hues than initially observed during continuous use. That is, when comparing the initial time with any other time, liquid crystal display devices using the wavelength conversion sheets of Patent Documents 3 and 4 frequently show significant differences in hue. Quantum dots are characterized by improved color purity. Therefore, hue instability in liquid crystal display devices using quantum dots detracts from the characteristics of the liquid crystal display device and is an extremely important quality issue.

[0020] In view of the above problems, the object of the present invention is to provide a barrier film that can suppress hue changes when applied to a wavelength conversion sheet. Furthermore, the object of the present invention is to provide a wavelength conversion sheet, a backlight, and a liquid crystal display device using the above-mentioned barrier film.

[0021] Methods for solving problems

[0022] To address the aforementioned issues, the inventors conducted in-depth research and discovered that when wavelength conversion sheets with barrier films are exposed to high humidity environments, the organic coating layer of the barrier film swells, which is one of the reasons for color tone changes. Therefore, the inventors investigated reducing the thickness of the organic coating layer without affecting its barrier properties. However, even with reduced thickness, color tone changes still frequently occurred.

[0023] Furthermore, the inventors conducted in-depth research and discovered that by setting the thickness of the organic coating layer to a predetermined range, and setting the ratio of the thickness of the undercoating layer (formed to improve adhesion to the quantum dot containing layer) to the thickness of the organic coating layer to a predetermined range, it is possible to suppress hue changes in wavelength conversion sheets, etc., to which a barrier film is applied.

[0024] The present invention provides the following [1] to [6].

[0025] [1] A barrier film for a wavelength conversion sheet, which has an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a base coating layer D sequentially on a light-transmitting substrate.

[0026] The thicknesses of the aforementioned translucent substrate, the aforementioned inorganic oxide layer A, the aforementioned organic coating layer B, the aforementioned inorganic oxide layer C, and the aforementioned base coating layer D are respectively defined as t0, t... A t B t C and t D hour,

[0027] t B For wavelengths between 150nm and 500nm, and...

[0028] t D / t B It is between 0.55 and 1.65.

[0029] [2] The barrier film as described in [1], wherein the inorganic oxide layer A and the inorganic oxide layer C comprise aluminum oxide or silicon oxide.

[0030] [3] The barrier film as described in [1] or [2], wherein the organic coating layer B comprises polyvinyl alcohol.

[0031] [4] A wavelength conversion sheet having a quantum dot containing a quantum dot and a barrier film laminated on both sides of the quantum dot containing a quantum dot, wherein the barrier film is laminated in such a way that the side of the barrier film opposite to the light-transmitting substrate is facing the side of the quantum dot containing a quantum dot as described in any one of [1] to [3].

[0032] [5] A backlight source comprising at least one light source emitting primary light, an optical plate disposed adjacent to the light source for guiding or diffusing light, and a wavelength conversion sheet disposed on the light emitting side of the optical plate, wherein the wavelength conversion sheet is the wavelength conversion sheet described in [4].

[0033] [6] A liquid crystal display device, which is a liquid crystal display device having a backlight and a liquid crystal panel, wherein the backlight is the backlight described in [5].

[0034] The effects of the invention

[0035] The barrier film of the present invention, as well as the wavelength conversion sheet, backlight and liquid crystal display device using the barrier film, can suppress color tone changes. Attached Figure Description

[0036] Figure 1 This is a cross-sectional view illustrating one embodiment of the barrier film of the present invention.

[0037] Figure 2 This is a cross-sectional view illustrating one embodiment of the wavelength conversion chip of the present invention.

[0038] Figure 3 This is a cross-sectional view illustrating one embodiment of the backlight of the present invention.

[0039] Figure 4 This is a cross-sectional view illustrating another embodiment of the backlight of the present invention. Detailed Implementation

[0040] The embodiments of the present invention will now be described.

[0041] It should be noted that in this instruction manual, the expression "AA~BB" refers to AA and above but BB and below.

[0042] Furthermore, in this specification, the refractive index of each layer refers to the refractive index at a wavelength of 632.8 nm. The refractive index of each layer can be calculated, for example, by fitting the reflectance spectrum measured by a reflectance photometer with the reflectance spectrum calculated using an optical model of a multilayer thin film with Fresnel coefficients.

[0043] [Barrier film]

[0044] The barrier film of the present invention comprises, in sequence, an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a base coating layer D on a light-transmitting substrate.

[0045] The thicknesses of the aforementioned translucent substrate, the aforementioned inorganic oxide layer A, the aforementioned organic coating layer B, the aforementioned inorganic oxide layer C, and the aforementioned base coating layer D are respectively defined as t0, t... A t B t C and t D hour,

[0046] t B For wavelengths between 150nm and 500nm, and...

[0047] t D / t B For values ​​between 0.55 and 1.65,

[0048] This barrier film was used in the wavelength conversion plate.

[0049] Figure 1 This is a cross-sectional view showing an embodiment of the barrier film (100) of the present invention. Figure 1 The barrier film (100) has an inorganic oxide layer A (21), an organic coating layer B (30), an inorganic oxide layer C (22), and a base layer D (40) sequentially on a light-transmitting substrate (10).

[0050] <Transparent substrate>

[0051] As a light-transmitting substrate, there are no particular restrictions as long as the resin film does not impair the function of the wavelength conversion sheet when used in conjunction with the wavelength conversion sheet.

[0052] Examples of light-transmitting substrates include resin films formed from one or more resins selected from polyester, triacetyl cellulose (TAC), cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl alcohol acetal, polyether ketone, acrylics, polycarbonate, polyurethane, and amorphous olefins (Cyclo-Olefin-Polymer: COP).

[0053] Among these resin films, polyester films that have undergone stretching, especially biaxial stretching, are preferred in terms of mechanical strength, dimensional stability, and heat resistance. Examples of polyester films include polyethylene terephthalate films and polyethylene naphthalate films.

[0054] The light-transmitting substrate can be a single-layer resin film or it can have two or more resin films. When there are two or more resin films, the resin films can be directly bonded together or bonded together through an adhesive layer.

[0055] The thickness t0 of the light-transmitting substrate is preferably 5 μm or more, more preferably 8 μm or more, and even more preferably 10 μm or more. By making the thickness of the light-transmitting substrate 5 μm or more, the strength of the barrier film can be easily improved.

[0056] Furthermore, from the perspective of thin film formation and easy suppression of water vapor and oxygen intrusion from the end, the thickness t0 of the light-transmitting substrate is preferably 200 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 50 μm or less, and more preferably 25 μm or less.

[0057] In this specification, the thickness of each layer constituting the barrier film, such as the thickness t0 of the light-transmitting substrate, and the thickness of the quantum dot-containing layer, can be determined, for example, by measuring the thickness at 20 points using a cross-sectional image taken with a scanning transmission electron microscope (STEM), and calculated from the average value of the values ​​at 20 points.

[0058] In this specification, unless otherwise specified, measurements of various parameters such as the thickness of each layer, total light transmittance, and hue (x and y values ​​of the Yxy chromaticity system) shall be conducted in an atmosphere with a temperature of 23℃ ± 5℃ and a relative humidity of 40% to 65%. Furthermore, the sample shall be exposed to the aforementioned atmosphere for at least 30 minutes before measuring any parameters.

[0059] It should be noted that when multiple upper and lower limit options for numerical values ​​are shown in the technical features described in this specification, one selected from the upper limit option can be combined with one selected from the lower limit option as an implementation of the numerical range. For example, in the case of the thickness t0 of the above-mentioned light-transmitting substrate, implementations with numerical ranges such as 5μm to 200μm, 5μm to 25μm, 8μm to 50μm, 10μm to 50μm, and 10μm to 25μm can be cited.

[0060] When the transparent substrate is composed of two resin films, the thickness of the first resin film on the side closest to the inorganic oxide layer A is preferably 5 μm or more and 50 μm or less, more preferably 8 μm or more and 25 μm or less, and even more preferably 10 μm or more and 20 μm or less. If the first resin film has the above-mentioned thickness, the manufacturing efficiency of the inorganic oxide layer can be easily improved, and the processability can be easily improved.

[0061] Furthermore, the thickness of the second resin film on the side furthest from the inorganic oxide layer A is preferably 5 μm to 150 μm, more preferably 8 μm to 100 μm, and even more preferably 10 μm to 50 μm. If the second resin film has the above-mentioned thickness, the balance between the processability and rigidity of the barrier film can be easily improved.

[0062] When a transparent substrate is composed of two resin films, the two resin films can be bonded together using an adhesive layer to form an inorganic oxide layer A, etc. Alternatively, an inorganic oxide layer A, etc., can be formed on the first resin film, and then a second resin film can be bonded to the side of the first resin film opposite to the inorganic oxide layer A, etc., using an adhesive layer. The thickness of the adhesive layer is preferably 3 μm or more and 100 μm or less, more preferably 3 μm or more and 50 μm or less, and even more preferably 4 μm or more and 8 μm or less. If the thickness of the adhesive layer is too thin, poor coating may sometimes occur; if the thickness is too thick, insufficient curing may sometimes occur.

[0063] The total light transmittance of the light-transmitting substrate according to JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 87% or more.

[0064] To improve adhesion, the surface of the transparent substrate on the side where the inorganic oxide layer A is located can be pre-treated with the desired surface treatment. Examples of surface treatments include corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen or nitrogen, glow discharge treatment, and oxidation treatment using chemicals.

[0065] <Inorganic oxide layer>

[0066] The barrier film of the present invention comprises an inorganic oxide layer A and an inorganic oxide layer C as inorganic oxide layers. Thus, by having two inorganic oxide layers, the barrier film's barrier properties against oxygen and water vapor can be improved, and the degradation of quantum dots can be easily suppressed. Furthermore, if only one inorganic oxide layer is used to improve barrier properties, the thickness of the inorganic oxide layer becomes too large, making it prone to cracking and thus difficult to improve barrier properties over a long period. However, by having two inorganic oxide layers, the thickness of each inorganic oxide layer can be suppressed, cracking is less likely, and barrier properties can be easily improved over a long period.

[0067] It should be noted that even when the thickness of the inorganic oxide layer is reduced, cracks or pinholes may sometimes occur. However, even if cracks or pinholes occur in both inorganic oxide layers, as long as the locations of the cracks or pinholes are not consistent in the planar direction, the laminate can still impart the required barrier properties. That is, by using two inorganic oxide layers, even if cracks or pinholes occur in the inorganic oxide layers, it is preferable from the perspective of easily imparting the required barrier properties.

[0068] Inorganic oxide layer A and inorganic oxide layer C can be exemplified as layers composed of one or a mixture of aluminum oxide, magnesium oxide, indium tin oxide (ITO), and silicon oxide. The compositions of inorganic oxide layer A and inorganic oxide layer C may be the same or different.

[0069] From the perspectives of transparency and productivity, inorganic oxide layer A and inorganic oxide layer C are preferably layers containing aluminum oxide or silicon oxide.

[0070] Furthermore, considering factors such as sufficient barrier properties, transparency, and productivity, it is preferable that at least one of the inorganic oxide layer A and the inorganic oxide layer C is a layer containing aluminum oxide, and more preferably both inorganic oxide layer A and inorganic oxide layer C are layers containing aluminum oxide.

[0071] The proportion of aluminum oxide or silicon oxide in inorganic oxide layer A or inorganic oxide layer C is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on a mass basis.

[0072] Examples of embodiments of the combination of inorganic oxide layer A and inorganic oxide layer C are as follows (1) to (4).

[0073] (1) Embodiment where inorganic oxide layer A and inorganic oxide layer C are both layers containing aluminum oxide.

[0074] (2) Embodiments where inorganic oxide layer A and inorganic oxide layer C are both layers containing silicon oxide.

[0075] (3) Embodiment where inorganic oxide layer A is a layer containing aluminum oxide and inorganic oxide layer C is a layer containing silicon oxide.

[0076] (4) Embodiment where inorganic oxide layer A is a layer containing silicon oxide and inorganic oxide layer C is a layer containing aluminum oxide.

[0077] Of the above (1) to (4), from the perspective of barrier properties, (1), (3) and (4) are preferred, and (1) is more preferred.

[0078] On the other hand, the barrier film is sometimes laminated with other components, and a specified tension is applied to the barrier film during lamination. In terms of crack resistance to the aforementioned tension, the layer containing silicon oxide is superior to the layer containing aluminum oxide. Therefore, from the perspective of crack resistance to the aforementioned tension, (2) to (4) are preferred, and (2) is more preferred.

[0079] In summary, from the perspective of balancing barrier properties and the tensile crack resistance of the inorganic oxide layer, (3) and (4) are preferred. Furthermore, compared to layers containing aluminum oxide, layers containing silicon oxide tend to generate pinholes more easily during the formation of inorganic oxide layers. Comparing (3) and (4), (4) is preferred from the perspective of easily maintaining barrier properties, even if pinholes are generated in the silicon oxide layer.

[0080] Inorganic oxide layers tend to have reduced barrier properties when too thin, and are prone to scratches and cracks when too thick. The thickness t of inorganic oxide layer A... A And the thickness t of the inorganic oxide layer C C Preferably, the inorganic oxide layer is within an appropriate range to achieve a good balance between barrier properties, scratch inhibition, and crack inhibition.

[0081] For example, when inorganic oxide layer A and inorganic oxide layer C are layers containing aluminum oxide, t A and t C The lower limit is preferably 6nm or more, and more preferably 7nm or more. By making t A and t C With a wavelength of 6nm or higher, barrier properties can be easily improved.

[0082] In addition, t A and t CThe upper limits are preferably 25nm or less, more preferably 20nm or less, more preferably 15nm or less, more preferably 12nm or less, and more preferably 10nm or less, respectively. By making t A and t C With a wavelength below 25nm, it can easily suppress scratches and cracks in inorganic oxide layers A and C.

[0083] Furthermore, when inorganic oxide layer A and inorganic oxide layer C are layers containing any one or more of silicon oxide, magnesium oxide, and indium tin oxide (ITO), t A and t C The lower limits are preferably 20 nm or more, more preferably 25 nm or more, and more preferably 27 nm or more. By making t A and t C With a wavelength of 20nm or more, barrier properties can be easily improved.

[0084] In addition, t A and t C The upper limits are preferably below 100nm, more preferably below 75nm, further preferably below 60nm, and even more preferably below 50nm. By making t A and t C With a wavelength below 100nm, it can easily suppress scratches and cracks in inorganic oxide layers A and C.

[0085] Inorganic oxide layers can be formed using physical vapor deposition methods such as vacuum evaporation, sputtering, and ion plating, or chemical vapor deposition methods such as plasma chemical vapor deposition, thermochemical vapor deposition, and photochemical vapor deposition. Among these, vacuum evaporation is preferred due to its fast deposition rate and high productivity.

[0086] <Organic Coating>

[0087] The barrier film of the present invention has an organic coating layer B as the organic coating layer. By having an organic coating layer in combination with the inorganic oxide layer, the barrier properties of the barrier film can be improved, and the degradation of quantum dots can be easily suppressed. In addition, the organic coating layer has better flexibility than the inorganic oxide layer; therefore, the organic coating layer B can easily suppress the formation of scratches and cracks in the inorganic oxide layers A and C. Preferably, the organic coating layer B is in contact with the inorganic oxide layers A and C in the thickness direction of the barrier film.

[0088] The thickness t of organic coating layer B B It needs to be between 150nm and 500nm. B Preferably, the wavelength is 175nm or higher and 450nm or lower, more preferably 200nm or higher and 400nm or lower.

[0089] In t B When the wavelength is less than 150nm, the barrier properties of the barrier film are insufficient, and the color tone changes over time due to the degradation of quantum dots in the quantum dot layer.

[0090] Additionally, in t B Beyond 500nm, while barrier effects are unlikely, hue variations cannot be suppressed. If t B The increase in thickness leads to a greater change in the thickness caused by the swelling of the organic coating layer B in a high-humidity environment. Therefore, the effect of thin-film interference changes significantly, and the waveform of the spectral transmittance of the barrier film shifts, thus rendering it unable to suppress hue changes. More specifically, the spectral transmittance value of the barrier film varies according to wavelength, increasing or decreasing at a predetermined period. Consequently, when the organic coating layer B swells and the waveform of the barrier film's spectral transmittance shifts towards longer or shorter wavelengths, the spectral transmittance at a specific wavelength (e.g., 450 nm) changes, thus altering the hue.

[0091] Additionally, if t B If the coating is too thick, the stress generated during the application and drying of the organic coating increases. Due to this stress, the inorganic oxide layer may sometimes crack, reducing its barrier properties. Therefore, by making t B With a wavelength below 500nm, it is easy to improve the initial barrier properties.

[0092] The organic coating layer B preferably comprises one or more selected from water-soluble polymers and metal alkoxide compounds. More preferably, the organic coating layer B comprises one or more selected from water-soluble polymers and metal alkoxide compounds, and even more preferably comprises one or more selected from water-soluble polymers and one or more selected from metal alkoxide compounds.

[0093] Examples of water-soluble polymers include polyvinyl alcohol, polyvinylpyrrolidone, and ethylene-vinyl alcohol copolymers. Among these, from a barrier properties perspective, polyvinyl alcohol and ethylene-vinyl alcohol copolymers are preferred, and polyvinyl alcohol is more preferred. That is, the organic coating layer B preferably contains one or more selected from polyvinyl alcohol and ethylene-vinyl alcohol copolymers, and more preferably contains polyvinyl alcohol.

[0094] When the organic coating layer B contains water-soluble polymers and metal alkoxide compounds, the content of water-soluble polymers relative to the total amount of metal alkoxide compounds is preferably 5 parts by mass or more and 500 parts by mass or less, more preferably 7 parts by mass or more and 100 parts by mass or less, and even more preferably 8 parts by mass or more and 50 parts by mass or less.

[0095] Examples of metal alkoxide compounds include metal alkoxides, metal alkoxide hydrolysates, and metal alkoxide polymers.

[0096] Metal alkoxides have the general formula M(OR). n The compounds shown are denoted by M, which represents metals such as Si, Ti, Al, and Zr, and R represents alkyl groups such as methyl and ethyl. Specific examples of metal alkoxides include tetramethoxysilane, tetraethoxysilane, and aluminum isopropoxysilane.

[0097] Organic coating layer B can be formed, for example, by applying a coating liquid containing the components constituting organic coating layer B onto an inorganic oxide layer and then drying it. The coating liquid may contain additives such as silane coupling agents, curing agents, and dispersants.

[0098] <Undercoat>

[0099] The barrier film of the present invention requires a base coating layer D on the side of the inorganic oxide layer C opposite to the organic coating layer B. By having the base coating layer, the adhesion between the barrier film and the quantum dot containing layer becomes better, and the barrier properties of the barrier film are easily maintained over a long period, thus suppressing color changes over time. Furthermore, the base coating layer D also makes it easier to suppress scratches and cracks in the inorganic oxide layer C.

[0100] The base coating is preferably disposed at a position in contact with the inorganic oxide layer C. Furthermore, the base coating is preferably disposed on the outermost layer of the barrier film.

[0101] The barrier film of this invention requires a base coating layer D with a thickness t. D With respect to the thickness t of the organic coating layer B B The ratio of t D / t B The range is between 0.55 and 1.65. t D / t B Preferably, the value is 0.60 or higher and 1.50 or lower, more preferably 0.70 or higher and 1.30 or lower.

[0102] In t D / t B When the value is less than 0.55, stress generated by the expansion and contraction of the barrier film will place excessive load on the thin base coating D, making the interface of the base coating D prone to peeling. Additionally, at t... D / t B When the value exceeds 1.65, stress generated by the expansion and contraction of the barrier film will apply excessive load to the thin organic coating layer B, making the interface of the organic coating layer B easy to peel off.

[0103] That is, by making t D / t B With a value between 0.55 and 1.65, it can suppress excessive load on either the organic coating layer B or the base layer D when stress is generated, thus easily maintaining the barrier properties of the barrier film for a long time and easily suppressing color changes over time.

[0104] The thickness t of the base coating D D As long as t D / t B The value can be between 0.55 and 1.65; there are no special restrictions.

[0105] t D Typically, the wavelength is 82.5nm or higher and 825nm or lower, preferably 100nm or higher and 600nm or lower, and more preferably 125nm or higher and 400nm or lower.

[0106] "composition"

[0107] The primer layer D preferably contains resin components such as a polyurethane-based resin composition. The polyurethane-based resin serves to: readily improve adhesion to the quantum dot-containing layer; and mitigate the stress generated during ionizing radiation curing or thermal curing of the quantum dot-containing layer, making it difficult for such stress to be transmitted to the inorganic oxide layer and the organic coating layer. Furthermore, by increasing the elongation of the primer layer D, the polyurethane-based resin can easily suppress cracking in the layers constituting the barrier film, such as the inorganic oxide layer.

[0108] Examples of polyurethane-based resin compositions include single-component or two-component polyurethane-based resin compositions obtained by reacting a polyfunctional isocyanate with a hydroxyl-containing compound. Only one type of polyfunctional isocyanate and one or more types of the hydroxyl-containing compound may be used.

[0109] Specifically, examples of polyfunctional isocyanates include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, phenyl dimethylene diisocyanate, and polymethylene polyphenylene polyisocyanate, as well as aliphatic polyisocyanates such as hexamethylene diisocyanate and isophorone diisocyanate.

[0110] In addition, examples of hydroxyl-containing compounds include polyether polyols, polyester polyols, polyester polyurethane polyols, and polyacrylate polyols. In this invention, polyester polyurethane polyols are particularly preferred from the perspective of adhesion and durability to the quantum dot containing layer. Polyester polyurethane polyols can be manufactured, for example, by the methods described in Japanese Patent Application Publication Nos. 2001-288408 and 2003-26996.

[0111] Based on the total amount of the base coating layer D, the content of the polyurethane resin composition is preferably 40% by mass or more, and more preferably 70% by mass or more.

[0112] The base layer D may further contain a silane coupling agent. By including a silane coupling agent, the adhesion between the base layer D and the inorganic oxide layer C can be easily improved. In the silane coupling agent, the functional group at one end of its molecule, typically chlorine, alkoxy, or acetoxy, undergoes hydrolysis to form a silanol group (Si-OH). Thus, the resin composition of the base layer D is modified through covalent bonds, forming a strong bond. Furthermore, the organic functional groups such as vinyl, methacryloxy, amino, epoxy, or mercapto groups at the other end of the silane coupling agent can easily improve the adhesion between the base layer D and the inorganic oxide layer C, as well as between the base layer D and the quantum dot containing layer.

[0113] Examples of silane coupling agents include γ-chloropropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyl-tris(β-methoxyethoxy)silane, γ-methacryloyloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-epoxypropoxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-ureidopropyltriethoxysilane, bis(β-hydroxyethyl)-γ-aminopropyltriethoxysilane, and γ-aminopropylsiloxane, etc., and one or more of them may be used.

[0114] Based on the total amount of the base coating layer D, the content of the silane coupling agent is preferably 1% by mass or more, more preferably 3% by mass or more. If the content of the silane coupling agent is within the above range, it is easy to further improve the adhesion between the base coating layer D and the inorganic oxide layer C, as well as between the base coating layer D and the quantum dot containing layer.

[0115] It should be noted that, in order to improve the elongation of the base coating D and suppress the formation of cracks in the base coating D, the content of the silane coupling agent is preferably 30% by mass or less, more preferably 20% by mass or less, based on the total amount of the base coating D.

[0116] The primer layer D may further contain fillers. Fillers have functions such as adjusting the viscosity of the coating liquid used to form the primer layer and improving coating adaptability. Examples of filler materials that can be used include calcium carbonate, barium sulfate, alumina white, silica, talc, glass powder, and resin powder.

[0117] The base coating may be further supplemented with stabilizers, crosslinking agents, lubricants, UV absorbers, and other additives as needed.

[0118] The total thickness of the inorganic oxide layer A, the organic coating layer B, the inorganic oxide layer C, and the base layer D is preferably 300 nm to 1200 nm, more preferably 400 nm to 900 nm, even more preferably 500 nm to 800 nm, and even more preferably 550 nm to 750 nm. By making the total thickness 300 nm or more, the barrier properties can be easily improved. In addition, by making the total thickness 1200 nm or less, the period of the spectral transmittance waveform can be suppressed from becoming too short. When the organic coating layer swells and the spectral transmittance waveform of the barrier film shifts to the longer or shorter wavelength side, large changes in spectral transmittance at a specific wavelength (e.g., wavelength 450 nm) can be easily suppressed.

[0119] <Physical properties>

[0120] Water vapor transmission rate

[0121] The water vapor transmission rate of the barrier membrane, based on JIS K7129-2:2019, is preferably 0.20 g / m³. 2 • Less than 1 day, preferably 0.15 g / m 2 • Less than 1 day. It should be noted that the temperature and humidity conditions for measuring water vapor transmission rate are 40℃ and 90% relative humidity. In addition, before measuring water vapor transmission rate, the sample to be measured should be exposed to an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% to 65% for more than 30 minutes.

[0122] Water vapor transmission rate can be measured, for example, using a water vapor transmission rate measuring device (trade name: PERMATRAN) manufactured by MOCON.

[0123] Oxygen permeability

[0124] The preferred oxygen permeability value of the barrier membrane based on JIS K7126-2:2006 is 0.5 cc / m. 2 • Days • below atm. It should be noted that the temperature and humidity conditions for measuring oxygen permeability are 23℃ and 90% relative humidity. Additionally, before measuring oxygen permeability, the sample to be measured should be exposed to an atmosphere at a temperature of 23℃±5℃ and a relative humidity of 40% to 65% for at least 30 minutes.

[0125] Oxygen permeability can be measured, for example, using an oxygen permeability measuring device (trade name: OX-TRAN) manufactured by MOCON (Mocon method).

[0126] b* value

[0127] L of the barrier membrane * a * b * b of the color system* The value is preferably -1.3 to 1.0, more preferably -1.5 to 0.8, and even more preferably -1.0 to 0.5. It should be noted that b * The value is the value of the b that is passed through. * Value. Additionally, the value of b was determined. * The light incident surface at the time of the value is the side opposite to the light-transmitting substrate.

[0128] L * a * b * The colorimetric system is based on the L-type standard standardized by the International Commission on Illumination (CIE) in 1976. * a * b * The colorimetric system is adopted in JIS Z8781-4:2013.

[0129] Total light transmittance

[0130] The total light transmittance of the barrier film according to JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 87% or more. It should be noted that the light incident surface when measuring the total light transmittance is the side opposite to the light-transmitting substrate.

[0131] <Laminated Structure>

[0132] Examples of the laminated structure of the barrier film of the present invention can be found in (1) below. In (1) below, " / " refers to the interface of the layers.

[0133] (1) Transparent substrate / Inorganic oxide layer A / Organic coating layer B / Inorganic oxide layer C / Undercoating layer D

[0134] Without impairing the effects of the present invention, the barrier film may have layers other than those described above.

[0135] The barrier film of the present invention can also be configured in the laminated structure described in (2) below. However, the laminated structure described in (2) below has more interfaces than that described in (1) above, which is disadvantageous from the perspective of optical properties, and the total thickness is also increased. Therefore, the laminated structure described in (1) above is preferred.

[0136] (2) First translucent substrate / inorganic oxide layer A / organic coating layer B / inorganic oxide layer C / second translucent substrate / base layer D

[0137] <Manufacturing Method>

[0138] Barrier films can be manufactured, for example, by sequentially forming an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a base coating layer D on a light-transmitting substrate.

[0139] As described above, inorganic oxide layer A and inorganic oxide layer C can be formed by physical vapor deposition or chemical vapor deposition, such as plasma chemical vapor deposition.

[0140] Organic coating layer B and primer layer D can be formed by applying a coating liquid containing the composition constituting each layer, drying it, and curing it as needed.

[0141] <Application>

[0142] The barrier film for the wavelength conversion sheet of the present invention can be used, for example, as a barrier film for a wavelength conversion sheet of a surface light source. Examples of surface light sources include backlight sources for liquid crystal display devices and backlight sources for inspection equipment. That is, the barrier film for the wavelength conversion sheet of the present invention can be used for "a barrier film for a wavelength conversion sheet of a backlight source of a liquid crystal display device" and "a barrier film for a wavelength conversion sheet of a backlight source of an inspection equipment", etc.

[0143] Furthermore, the barrier film for the wavelength conversion sheet of the present invention can also be used as a "barrier film for wavelength conversion sheets in horticulture." Examples of wavelength conversion sheets for horticulture include sheets that convert ultraviolet light into wavelengths suitable for plant growth. Examples of wavelengths suitable for plant growth include wavelengths suitable for photosynthesis. For example, wavelength conversion sheets for horticulture can be installed on the ceilings of horticultural facilities such as plastic greenhouses and glasshouses.

[0144] Wavelength conversion plate

[0145] The wavelength conversion sheet of the present invention is a wavelength conversion sheet having a quantum dot containing a quantum dot and a barrier film laminated on both sides of the quantum dot containing the quantum dot, wherein the barrier film of the present invention, which serves as the barrier film, is laminated such that the side opposite to the light-transmitting substrate faces the side of the quantum dot containing the quantum dot.

[0146] Figure 2 This is a cross-sectional view showing an embodiment of the wavelength conversion chip (200) of the present invention. Figure 2 The wavelength conversion sheet (200) has a quantum dot containing layer (50) and barrier films (100a, 100b) laminated on both sides of the quantum dot containing layer. Additionally, Figure 2 The wavelength conversion sheet (200) was laminated with the side of the barrier film (100a, 100b) opposite to the light-transmitting substrate (10) facing the side containing the quantum dot layer (50).

[0147] like Figure 2As shown, the wavelength conversion sheet preferably has a symmetrical configuration with the quantum dot containing layer at its center. In other words, the barrier films laminated on both sides of the quantum dot containing layer preferably use barrier films with the same configuration. With the above configuration, strain is evenly distributed, which can easily improve the planarity of the wavelength conversion sheet and the adhesion of each interface of the wavelength conversion sheet.

[0148] <Quantum dot containing layer>

[0149] The quantum dot layer contains quantum dots and a binder resin.

[0150] Quantum dots are nanoscale particles of semiconductors that exhibit unique optical and electrical properties through the quantum confinement effect (quantum size effect) in which electrons and excitons are encapsulated within tiny nanoscale crystals. They are also known as semiconductor nanoparticles or semiconductor nanocrystals.

[0151] Quantum dots are nanoscale particles of semiconductors, and there are no particular limitations as long as the material produces a quantum confinement effect (quantum size effect). Examples of quantum dots include semiconductor particles whose emission color is limited by their own particle size and semiconductor particles with dopants.

[0152] Quantum dots emit different colors of light depending on their particle size. For example, in the case of quantum dots composed solely of a CdSe core, the peak wavelengths of their fluorescence spectra with particle sizes of 2.3 nm, 3.0 nm, 3.8 nm, and 4.6 nm are 528 nm, 570 nm, 592 nm, and 637 nm, respectively. That is, the quantum dot emitting secondary light with a peak wavelength of 637 nm has a particle size of 4.6 nm, while the quantum dot emitting secondary light with a peak wavelength of 528 nm has a particle size of 2.3 nm.

[0153] The quantum dots preferably include one or more selected from quantum dots that emit secondary light at a wavelength corresponding to red and quantum dots that emit secondary light at a wavelength corresponding to green, and more preferably include quantum dots that emit secondary light at a wavelength corresponding to red and quantum dots that emit secondary light at a wavelength corresponding to green.

[0154] Quantum dots can include quantum dots that emit secondary light at a wavelength corresponding to red, and quantum dots that emit secondary light at a wavelength corresponding to green, in addition to those that emit secondary light at a wavelength corresponding to green.

[0155] The quantum dot content is adjusted appropriately based on the thickness of the quantum dot layer, the light recycling rate in the backlight, and the target hue. If the thickness of the quantum dot layer is within the range described later, the quantum dot content is approximately 0.01 to 1.0 parts by mass relative to 100 parts by mass of the adhesive resin in the quantum dot layer.

[0156] Specifically, examples of semiconductor materials that can serve as the core of quantum dots include semiconductor compounds or semiconductor crystals containing group II-VI semiconductor compounds such as MgS, MgSe, MgTe, CaS, CaSe, CaTe, SrS, SrSe, SrTe, BaS, BaSe, BaTe, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, HgS, HgSe, and HgTe; group III-V semiconductor compounds such as AlN, AlP, AlAs, AlSb, GaAs, GaP, GaN, GaSb; group IV semiconductors such as InN, InAs, InP, InSb; TiN, TiP, TiAs, and TiSb; and group IV semiconductors such as Si, Ge, and Pb. Alternatively, semiconductor crystals containing semiconductor compounds with three or more elements, such as InGaP, can also be used.

[0157] Furthermore, as quantum dots composed of semiconductor particles with dopants, Eu-doped semiconductor compounds described above can also be used. 3+ 、Tb 3+ Ag + Cu + Semiconductor crystals of rare earth metal cations or transition metal cations.

[0158] As materials for quantum dots, semiconductor crystals such as CdS, CdSe, CdTe, InP, and InGaP are preferred from the perspectives of ease of fabrication, controllability of particle size for obtaining visible light emission, and fluorescence quantum yield.

[0159] Quantum dots can be composed of one semiconductor compound or two or more semiconductor compounds. For example, they can have the following core-shell structure: the core-shell structure has a core composed of a semiconductor compound and a shell composed of a semiconductor compound different from the core.

[0160] When using core-shell quantum dots, the luminescence efficiency of the quantum dots can be improved by using a semiconductor material with a band gap higher than that of the semiconductor compound forming the core, so that excitons are encapsulated in the core.

[0161] Examples of core-shell structures (core / shell) with this bandgap size relationship include CdSe / ZnS, CdSe / ZnSe, CdSe / CdS, CdTe / CdS, InP / ZnS, Gap / ZnS, Si / ZnS, InN / GaN, InP / CdSSe, InP / ZnSeTe, InGaP / ZnSe, InGaP / ZnS, Si / AlP, InP / ZnSTe, InGaP / ZnSTe, and InGaP / ZnSSe.

[0162] To obtain light at the desired wavelength, the size of the quantum dots can be appropriately controlled by the materials that constitute them. As the particle size of the quantum dots decreases, the band gap increases. That is, as the crystal size decreases, the emission of the quantum dots shifts towards the blue side, i.e., the high-energy side. Therefore, by changing the size of the quantum dots, their emission wavelength can be tuned across the entire spectrum in the ultraviolet, visible, and infrared regions.

[0163] Generally, the particle size (diameter) of quantum dots is preferably in the range of 0.5 nm to 20 nm, and particularly preferably in the range of 1 nm to 10 nm. It should be noted that the narrower the size distribution of quantum dots, the clearer the emission color can be obtained.

[0164] The shape of quantum dots is not particularly limited and can be, for example, spherical, rod-shaped, disk-shaped, or other shapes. Regarding the particle size of quantum dots, when the quantum dots are not spherical, they can be the size of a perfectly spherical dot with the same volume.

[0165] Quantum dots can be coated with resin.

[0166] Examples of adhesive resins that can be used as quantum dot-containing layers include thermoplastic resins, cured thermosetting resin compositions, and cured ionizing radiation-curable resin compositions. Among these, cured thermosetting resin compositions and cured ionizing radiation-curable resin compositions are preferred from a durability perspective, and cured ionizing radiation-curable resin compositions are more preferred.

[0167] The thermosetting resin composition is a composition comprising at least a thermosetting resin, and is a resin composition that is cured by heating. Preferably, the thermosetting resin composition also comprises a thiol compound (described later) in addition to the thermosetting resin, and more preferably comprises a polyfunctional thiol compound.

[0168] Examples of thermosetting resins include acrylic resins, urethane resins, phenolic resins, urea-melamine resins, epoxy resins, unsaturated polyester resins, and silicone resins. In thermosetting resin compositions, curing agents can be added to these curing resins as needed.

[0169] The ionizing radiation-curable resin composition is a composition comprising a compound having an ionizing radiation-curable functional group (hereinafter also referred to as "ionizing radiation-curable compound"). Preferably, the ionizing radiation-curable resin composition also comprises a thiol compound (described later) in addition to the ionizing radiation-curable compound, and more preferably comprises a polyfunctional thiol compound.

[0170] Examples of ionizing radiation curable functional groups include olefinic unsaturated groups such as (meth)acryloyl, vinyl, and allyl, as well as epoxy and oxetyl groups, with olefinic unsaturated groups being preferred. Among olefinic unsaturated groups, (meth)acrylate groups are preferred. Hereinafter, ionizing radiation curable compounds having a (meth)acryloyl group will be referred to as (meth)acrylate compounds. That is, the adhesive resin preferably includes a cured product containing a composition of a (meth)acrylate compound.

[0171] It should be noted that in this specification, "(meth)acrylate" refers to methacrylate and acrylate. Additionally, in this specification, "ionizing radiation" refers to ionizing radiation in electromagnetic waves or charged particle beams that possesses energy quanta capable of polymerizing or cross-linking molecules. Ultraviolet light or electron beams are commonly used; however, X-rays, gamma rays, and other electromagnetic waves, alpha rays, and ion beams can also be used.

[0172] The ionizing radiation curable compound can be a monofunctional ionizing radiation curable compound having only one of the aforementioned functional groups, or a polyfunctional ionizing radiation curable compound having two or more of the aforementioned functional groups, or a mixture of these compounds. Among these, polyfunctional ionizing radiation curable compounds are preferred, and polyfunctional (meth)acrylate compounds having two or more (meth)acryloyl groups are more preferred. That is, the adhesive resin preferably contains a cured product of a polyfunctional ionizing radiation curable compound, and more preferably a cured product containing a polyfunctional (meth)acrylate compound. Furthermore, the adhesive resin preferably contains a cured product of a composition containing a polyfunctional ionizing radiation curable compound and a thiol compound, and more preferably a cured product of a composition containing a polyfunctional (meth)acrylate compound and a thiol compound.

[0173] Polyfunctional (meth)acrylate compounds can have alkylene oxides.

[0174] As an alkylene oxide, for example, an alkylene oxide with 2 or more to 4 carbon atoms is preferred, an alkylene oxide with 2 or 3 carbon atoms is more preferred, and an alkylene oxide with 2 carbon atoms is even more preferred.

[0175] Polyfunctional (meth)acrylate compounds having alkylene oxides can be polyfunctional (meth)acrylate compounds having polyalkylene oxides containing multiple alkylene oxides.

[0176] When the polyfunctional (meth)acrylate compound has alkylene groups, the number of alkylene groups in one molecule is preferably 2 or more but less than 30, more preferably 2 or more but less than 20, further preferably 3 or more but less than 10, and even more preferably 3 or more but less than 5.

[0177] When a polyfunctional (meth)acrylate compound has an alkylene group, it is preferable to have a bisphenol structure. This tends to improve the heat resistance of the cured product. Examples of bisphenol structures include bisphenol A and bisphenol F, with bisphenol A being preferred.

[0178] As a polyfunctional (meth)acrylate compound having an alkylene oxide, ethoxylated bisphenol A type di(meth)acrylate, propoxylated bisphenol A type di(meth)acrylate and propoxylated ethoxylated bisphenol A type di(meth)acrylate are preferred, and ethoxylated bisphenol A type di(meth)acrylate is more preferred.

[0179] In addition, ionizing radiation-curable compounds can be monomers, oligomers, low molecular weight polymers, or mixtures of these substances.

[0180] As described above, the thermosetting resin composition and the ionizing radiation-curable resin composition preferably contain a thiol compound.

[0181] Thiols are compounds having one or more units represented by R-SH (where R is an organic group). In this specification, compounds having one unit represented by R-SH are referred to as monofunctional thiols, and compounds having two or more units represented by R-SH are referred to as polyfunctional thiols.

[0182] The thiol compound can be a monofunctional thiol compound, but from the perspective of improving the strength of the quantum dot containing layer, a polyfunctional thiol compound is preferred. Furthermore, among polyfunctional thiol compounds, a trifunctional or tetrafunctional thiol compound is more preferred.

[0183] In the presence of a free radical polymerization initiator, a thiol compound undergoes a thiol-ene reaction with a compound having free radical polymerizable functional groups, as shown in the formula below. This thiol-ene reaction suppresses polymerization shrinkage, thus mitigating stress generated during the curing of the quantum dot containing layer. Consequently, it is easier to further improve the interlayer adhesion of the wavelength conversion sheet, which is preferable from this perspective. Furthermore, from the perspective of easily improving heat resistance, the cured product obtained through the thiol-ene reaction is preferred. In addition, the refractive index of the thiol compound (approximately 1.53) is higher than that of the polyfunctional (meth)acrylate compound (approximately 1.45), thus increasing the degree of freedom in adjusting the refractive index of the quantum dot containing layer.

[0184] It should be noted that the following reaction is an example of a monofunctional thiol compound reacting with a compound having one free radical polymerizable functional group. It is believed that the reactants of polyfunctional thiol compounds and compounds having two or more free radical polymerizable functional groups readily form dendritic polymer structures. Furthermore, in the case of the formation of a dendritic polymer structure, it is believed that the flexibility of the quantum dot containing layer increases, and the quantum dot containing layer itself readily exhibits excellent stress relaxation properties. Examples of free radical polymerizable functional groups include (meth)acryloyl, vinyl, allyl, and other groups containing olefinic unsaturated bonds.

[0185] [Chemistry 1]

[0186]

[0187] [In the formula, R] 1 and R 2 It is an organic group.

[0188] Specific examples of monofunctional thiols include hexamethylenetetramine, 1-heptanethiol, 1-octanethiol, 1-nonanethiol, 1-decanethiol, 3-mercaptopropionic acid, methyl mercaptopropionate, methoxybutyl mercaptopropionate, octyl mercaptopropionate, tridecyl mercaptopropionate, 2-ethylhexyl 3-mercaptopropionate, and n-octyl 3-mercaptopropionate.

[0189] Specific examples of polyfunctional thiols include ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), 1,2-propanediol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptobutyrate), 1,4-butanediol bis(3-mercaptopropionate), 1,4-butanediol bis(3-mercaptobutyrate), 1,8-octanediol bis(3-mercaptopropionate), 1,8-octanediol bis(3-mercaptobutyrate), hexanediol dimercaptoacetate, trimethylolpropane tri(3-mercaptopropionate), trimethylolpropane tri(3-mercaptobutyrate), trimethylolpropane tri(3-mercaptoisobutyrate), and trimethylolpropane tri(3-mercaptoisobutyrate). Trimethylolpropane trimercaptoacetate, trimethylolpropane trimercaptoacetate, tri-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, trimethylolpropane trimercaptoacetate, pentaerythritol tetramercaptopropionate, pentaerythritol tetramercaptoacetate, pentaerythritol tetramercaptoacetate, pentaerythritol tetramercaptoacetate, pentaerythritol tetramercaptoacetate, dipentaerythritol hexamercaptoacetate, dipentaerythritol hexamercaptoacetate, dipentaerythritol hexamercaptoacetate, dipentaerythritol tetramercaptoacetate, dipentaerythritol hexamercaptoacetate, etc.

[0190] In the ionizing radiation curable resin composition (or thermosetting resin composition), the mass ratio of the ionizing radiation curable compound (or thermosetting resin) to the thiol compound is preferably 80:20 to 35:65, more preferably 70:30 to 40:60.

[0191] When the ionizing radiation curable compound is an ultraviolet curable compound, the ionizing radiation curable composition preferably contains additives such as photopolymerization initiators and photopolymerization accelerators.

[0192] Quantum dots contain layers that can contain internally diffused particles.

[0193] Internally diffused particles can be either organic or inorganic particles. Examples of organic particles include those composed of polymethyl methacrylate, acrylic-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, guanidine-melamine-formaldehyde condensate, silicone resin, fluorinated resin, and polyester. Examples of inorganic particles include those composed of silica, alumina, zirconium oxide, and titanium dioxide.

[0194] Internally diffused particles can take various shapes, including spherical, disc-shaped, rugby ball-shaped, and amorphous. Furthermore, internally diffused particles can be hollow, porous, or solid particles.

[0195] The content of internally diffused particles is preferably 1 part to 40 parts by mass, more preferably 3 parts to 30 parts by mass, relative to 100 parts by mass of the binder resin.

[0196] The average particle size of the internally diffused particles is preferably 1 μm or more and 7 μm or less, more preferably 1 μm or more and 3 μm or less.

[0197] The thickness of the quantum dot layer is preferably 10 μm to 200 μm, more preferably 20 μm to 150 μm, and even more preferably 30 μm to 130 μm.

[0198] The refractive index n of the quantum dot layer Z Preferably, the value is 1.40 or higher and 1.55 or lower; more preferably, 1.43 or higher and 1.52 or lower; and even more preferably, 1.46 or higher and 1.50 or lower.

[0199] The refractive index n of the quantum dot layer Z The refractive index is largely controlled by the adhesive resin. This is because the quantum dot layer contains a small amount of quantum dots, and even if an internal diffusing agent is included, the particle size of the internal diffusing agent is larger than the wavelength of light and will not affect the refractive index of the layer.

[0200] [Backlight]

[0201] The backlight of the present invention includes at least one light source that emits primary light, an optical plate for guiding or diffusing light arranged adjacent to the light source, and a wavelength conversion sheet arranged on the light emitting side of the optical plate. In this backlight, the wavelength conversion sheet is the wavelength conversion sheet of the present invention.

[0202] As an example of the backlight 300 of the present invention, the following can be cited: Figure 3 The edge-lit type backlight 301 shown, or Figure 4 The direct-lit backlight 302 shown.

[0203] Figure 3 The optical plate 220 used in the edge-lit backlight 301 is an optical component used to guide the primary light emitted by the light source 210, and is called a light guide plate 221. The light guide plate 221 is, for example, formed in a generally flat shape such that at least one surface is the light incident surface and another surface that is approximately orthogonal to it is the light emitting surface.

[0204] The light guide plate is mainly composed of a matrix resin selected from highly transparent resins such as polymethyl methacrylate. Resin particles with different refractive indices than the matrix resin can be added to the light guide plate as needed. The surfaces of the light guide plate can have complex shapes instead of uniform planes, and can also have dotted patterns, etc.

[0205] Figure 4 The optical plate 220 used in the direct-lit backlight 302 is an optical component (light diffuser 222) that has light diffuser properties to make the pattern of the light source 210 difficult to see. As a light diffuser 222, an example is a milky white resin plate with a thickness of about 1 mm to 3 mm.

[0206] In edge-lit and direct-lit backlights, in addition to the aforementioned light source, optical plate, and barrier film, one or more components selected from reflective plates, light-diffusing films, prism sheets, brightness enhancement films (BEF), and reflective polarizing films (DBEF) may be provided depending on the purpose.

[0207] A reflector is disposed on the side of the optical plate opposite to the light-emitting surface. A light-diffusing film, a prism sheet, a brightness enhancement film, and a reflective polarizing film are disposed on the light-emitting surface side of the optical plate. By incorporating one or more components selected from a reflector, a light-diffusing film, a prism sheet, a brightness enhancement film, and a reflective polarizing film, a backlight source with excellent balance in terms of front brightness and viewing angle can be manufactured.

[0208] In edge-lit and direct-lit backlights, the light source 210 is a light emitter that emits primary light, preferably a light emitter that emits primary light with a wavelength corresponding to blue. The peak wavelength of the primary light corresponding to the blue wavelength is preferably in the range of 380 nm to 480 nm. More preferably, the peak wavelength is 450 nm ± 7 nm, more preferably 450 nm ± 5 nm, more preferably 450 nm ± 3 nm, and more preferably 450 nm ± 1 nm.

[0209] From the perspective of simplifying and miniaturizing the device for setting the backlight, LED light source is preferred as the light source 210, and blue monochromatic LED light source is more preferred. There is at least one light source 210, and from the perspective of emitting sufficient primary light, two or more are preferred.

[0210] Regarding the International Commission on Illumination (CIE) Yxy chromaticity system, the difference in x-value (Δx) and y-value (Δy) of the backlight including the wavelength conversion sheet before and after the following high temperature and high humidity test is preferably 0.015 or less, and more preferably 0.010 or less. By making Δx and Δy 0.020 or less, hue changes can be suppressed.

[0211] High temperature and high humidity test: a test involving exposure to an atmosphere of 60°C and 90% relative humidity for 1000 hours.

[0212] It should be noted that the x and y values ​​after the high temperature and high humidity test should be measured quickly in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% to 65% after the sample is removed from the high temperature and high humidity test environment.

[0213] Liquid crystal display device

[0214] The liquid crystal display device of the present invention is a liquid crystal display device having a backlight and a liquid crystal panel, wherein the backlight is the backlight of the present invention.

[0215] There are no particular limitations on the liquid crystal panel; any liquid crystal panel commonly used in liquid crystal display devices can be used. For example, a liquid crystal panel with a general structure in which the liquid crystal layer is sandwiched between two glass plates can be used. Specifically, liquid crystal panels with display methods such as TN, STN, VA, IPS, and OCB can be used.

[0216] Liquid crystal display devices further incorporate polarizers and color filters. Polarizers and color filters can use common materials.

[0217] The image displayed in a liquid crystal display (LCD) device is colored by passing white light illuminating a backlight through a color filter. By using a color filter that is compatible with the spectrum of a quantum dot-based backlight, the LCD device can achieve a display with excellent brightness and efficiency, capable of producing very vivid colors.

[0218] Example

[0219] The invention will now be described in more detail through examples, but the invention is not limited to these examples in any way. It should be noted that, unless otherwise stated, "parts" and "%" are based on mass.

[0220] 1. Measurement and evaluation

[0221] The following measurements and evaluations were performed on the barrier films or wavelength conversion sheets of the Examples and Comparative Examples. The results are shown in Tables 1 and 2.

[0222] 1-1. Water vapor transmission rate

[0223] Regarding the barrier membranes of the examples and comparative examples, the water vapor transmission rate was measured based on JIS K7129-2:2019. The measuring apparatus used was a MOCON product, trade name "PERMATRAN". The temperature and humidity conditions for measuring the water vapor transmission rate were 40°C and 90% relative humidity. Furthermore, before measuring the water vapor transmission rate, the samples were exposed to an atmosphere at a temperature of 23°C ± 5°C and a relative humidity of 40% to 65% for at least 30 minutes. The water vapor transmission rate measured in this way refers to the water vapor transmission rate in the initial stage. The water vapor transmission rate was 0.20 g / m³. 2 • A level below 1 day is considered acceptable.

[0224] 1-2. Total light transmittance

[0225] The total light transmittance was measured for the barrier films of the examples and comparative examples. The light incident surface was the side opposite to the light-transmitting substrate. A haze meter (HM-150, manufactured by Murakami Color Technology Research Institute) was used for the measurement. A total light transmittance of 85% or higher was considered acceptable.

[0226] It should be noted that the total light transmittance was measured in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% to 65%. Furthermore, the sample was exposed to this atmosphere for at least 30 minutes before measurement. The total light transmittance measured in this way refers to the total light transmittance in the initial stage.

[0227] 1-3.b * value

[0228] Regarding the barrier films of the examples and comparative examples, L was measured. * a * b * b of the color system * Value (through b) * (Value). The light incident surface is the side opposite to the translucent substrate. The measuring apparatus used is a spectrophotometer (trade name: V670) manufactured by Nippon Spectrophotometer Co., Ltd.* A value between -1.3 and 1.0 is considered acceptable.

[0229] It should be noted that b * The value was measured in an atmosphere with a temperature of 23℃±5℃ and a relative humidity of 40% to 65%. Furthermore, the sample was exposed to this atmosphere for at least 30 minutes before measurement. The value of b obtained in this way... * The value refers to b in the initial stage. * value.

[0230] 1-4. Δx, Δy

[0231] <Preparation of the direct-lit backlight for measurement>

[0232] Disassemble a commercially available LCD TV (VIZIO PQ65-F1) equipped with a direct-lit backlight and remove the direct-lit backlight. This direct-lit backlight uses a direct-lit blue LED with a center wavelength of 450nm and a full width at half maximum (FWHM) of 20nm as the light source. Additionally, on the light-emitting side of this light source, a light diffuser, a wavelength conversion sheet containing a quantum dot layer, a prism sheet, and a reflective polarizer (brightness enhancement film, 3M, DBEF (registered trademark)) are arranged sequentially. Furthermore, a reflective sheet is provided on the side of the light source opposite to the light-emitting side.

[0233] By replacing the wavelength conversion sheet in the aforementioned direct-lit backlight with the wavelength conversion sheets of the Examples and Comparative Examples, a "direct-lit backlight for measuring x and y values ​​in the initial stage" was obtained. It should be noted that the wavelength conversion sheets of the Examples and Comparative Examples were exposed to an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% to 65% for more than 30 minutes before being assembled into the direct-lit backlight.

[0234] Furthermore, the wavelength conversion element in the aforementioned direct-lit backlight was replaced with the wavelength conversion element of the examples and comparative examples that underwent a high-temperature and high-humidity test (exposure for 1000 hours in an atmosphere of 60°C and 90% relative humidity), resulting in a "direct-lit backlight for measuring x and y values ​​after the high-temperature and high-humidity test". The assembly of the wavelength conversion elements of the examples and comparative examples that underwent the high-temperature and high-humidity test into the direct-lit backlight was rapidly performed in an atmosphere of 23°C ± 5°C and relative humidity between 40% and 65%.

[0235] Furthermore, the direct-lit backlight used in the above measurements was measured under the following conditions.

[0236] <Initial stage x and y values>

[0237] A direct-lit backlight was used to measure the x and y values ​​during the initial illumination phase. The measurements were taken in a darkroom environment from a distance of 500 mm from the front, using the International Commission on Illumination (CIE) Yxy chromaticity system. The measurement atmosphere was 23℃ ± 5℃ and relative humidity between 40% and 65%. The samples were exposed to this atmosphere for at least 30 minutes before measurement. The measurement apparatus used was a spectroradiometer (trade name: SR-3AR) manufactured by Topcon Technohouse.

[0238] <x and y values ​​after high temperature and high humidity test>

[0239] A direct-lit backlight was used to measure the x and y values ​​of the Yxy chromaticity system according to the International Commission on Illumination (CIE) in a darkroom environment, from a distance of 500 mm from the front. The measurement atmosphere was 23℃±5℃ and relative humidity between 40% and 65%. The measuring apparatus used was a spectroradiometer (trade name: SR-3AR) manufactured by Topcon Technohouse.

[0240] <Δx、Δy>

[0241] Calculate the difference (Δx) between the x-value in the initial stage and the x-value after the high temperature and humidity test, and the difference (Δy) between the y-value in the initial stage and the y-value after the high temperature and humidity test. A value below 0.015 for both Δx and Δy is considered acceptable.

[0242] 2. Preparation of quantum dot dispersion

[0243] In a glove box purged with nitrogen to a concentration below 300 ppm, quantum dots and amino-modified silicone were mixed at the composition ratio shown below, and stirred magnetically for 4 hours while being heated in hot water at 90°C. The mixture was then filtered through a polypropylene filter with a pore size of 0.2 μm to obtain a CdSe / ZnS core-shell quantum dot dispersion.

[0244] ·0.9 parts by mass of quantum dots

[0245] (Emission peak: 540nm, Manufacturing number: 748056, Manufactured by SigmaAldrich)

[0246] ·0.9 parts by mass of quantum dots

[0247] (Emission peak: 630nm, Manufacturing number: 790206, Manufactured by SigmaAldrich)

[0248] 99 parts by weight of amino-modified silicone

[0249] (Manufactured by Genesee, Product No.: GP-344, Viscosity: 670 mPa·s)

[0250] 3. Fabrication of the barrier film and the wavelength conversion plate

[0251] [Example 1]

[0252] Alumina was deposited on one side of a biaxially oriented PET film (refractive index n0: 1.636, thickness t0: 12 μm) using vacuum evaporation to form an inorganic oxide layer A (refractive index n0: 1.636, thickness t0: 12 μm). A 1.77, thickness t A (8nm).

[0253] Next, the following organic coating layer forming solution is applied to the inorganic oxide layer A by gravure printing, and then heated at 180°C for 60 seconds to form the organic coating layer B (refractive index n). B 1.55, thickness t B (219nm).

[0254] Next, aluminum oxide is deposited on the organic coating layer B by vacuum evaporation to form an inorganic oxide layer C (refractive index n). C 1.77, thickness t C (8nm).

[0255] Next, the following base coating forming liquid 1 is applied to the inorganic oxide layer C by gravure printing, and then heated at 80°C for 60 seconds to form the base coating D (refractive index n). D 1.575, thickness t E (270nm) was used to obtain the barrier film of Example 1. It should be noted that two barrier films with the same composition were fabricated.

[0256] <Preparation of Coating Solution for Organic Coating Formation>

[0257] Solution A was prepared by mixing tetraethoxysilane with a solution containing water, isopropanol, and 0.5N hydrochloric acid (pH 2.2) while cooling to 10°C. Solution B was separately prepared by mixing polyvinyl alcohol (PVA) with a saponification value of 99% or higher and isopropanol. Solutions A and B were mixed to prepare a coating solution for forming an organic coating layer (solid content: 5% by mass). In the coating solution for forming the organic coating layer, the mass ratio of tetraethoxysilane to PVA was 29:4.

[0258] <Coating liquid for forming the base layer>

[0259] ·50 parts by weight of polyester polyurethane polyol

[0260] (Hydroxy value: 62 mg KOH / g, solid content 20% by mass)

[0261] · 1 part by weight of silane coupling agent

[0262] (3-Epoxypropoxypropylmethyldimethoxysilane)

[0263] · 1 part by weight of silica filler

[0264] (Average particle size 5μm)

[0265] · 1 part by weight of curing agent

[0266] (1,6-Hexamethylene diisocyanate, 35% solids)

[0267] · 50 parts by weight of solvent

[0268] (Methyl ethyl ketone)

[0269] The quantum dot-containing layer coating liquid of the following formulation is coated on the undercoat side of one of the two barrier films prepared above and then dried to obtain a laminate A with a quantum dot-containing layer formed by ionizing radiation-free radiation.

[0270] Next, lamination was performed with the side of the quantum dot-containing layer that was not irradiated by ionizing rays of laminate A facing the side of the undercoat layer of another barrier film. Then, ultraviolet light was irradiated to cure the ionizing ray-curable resin composition of the quantum dot-containing layer, resulting in the wavelength conversion sheet of Example 1. The thickness of the quantum dot-containing layer was 100 μm, and the refractive index was 1.48.

[0271] <Quantum dots contain a coating solution>

[0272] · 58.11 parts by weight of multifunctional acrylate compounds

[0273] (Ethoxylated bisphenol A diacrylate: trade name "ABE-300" of Shin-Nakamura Chemical Industry Co., Ltd.)

[0274] · 38.74 parts by weight of polyfunctional thiols

[0275] (Pentaerythritol tetra(3-mercaptopropionate): trade name "PEMP" from SC Organic Chemistry)

[0276] • 0.5 parts by weight of photopolymerization initiator

[0277] (IGM Resins BV's product name "Omnirad TPO H")

[0278] • 1.61 parts by mass of the quantum dot dispersion prepared in step “2” above

[0279] Acetic acid 0.79 parts by weight

[0280] 0.25 parts by weight of titanium dioxide

[0281] (Chemours' trade name "Ti-Pure R-706": particle size 0.36μm)

[0282] [Examples 2-14]

[0283] The thicknesses of the organic coating layer B and the base coating layer D were changed to the values ​​in Table 1. Otherwise, the barrier films and wavelength conversion sheets of Examples 2 to 14 were obtained in the same manner as in Example 1.

[0284] In Examples 9-14, the base coating was formed using a base coating forming coating liquid 2. Furthermore, the refractive index n of the base coatings in Examples 9-14... D It is 1.58.

[0285] <Coating liquid for forming the base layer>

[0286] ·50 parts by weight of polyester polyurethane polyol

[0287] (Hydroxy value: 52 mg KOH / g, solid content 20% by mass)

[0288] · 1 part by weight of silane coupling agent

[0289] (3-Epoxypropoxypropylmethyldimethoxysilane)

[0290] · 1 part by weight of silica filler

[0291] (Average particle size 5μm)

[0292] · 1 part by weight of curing agent

[0293] (1,3-Xylene diisocyanate, 35% solids)

[0294] · 50 parts by weight of solvent

[0295] (Methyl ethyl ketone)

[0296] [Examples 15-16]

[0297] The inorganic oxide layers A and C were replaced with a silicon dioxide vapor-deposited film (refractive index: 1.457), and the thicknesses of the inorganic oxide layer A, organic coating layer B, inorganic oxide layer C, and base layer D were changed to the values ​​in Table 1. Otherwise, the barrier films and wavelength conversion sheets of Examples 15 and 16 were obtained in the same manner as in Example 1.

[0298] [Comparative Example 1]

[0299] An undercoat layer D is formed on the organic coating layer B, but no inorganic oxide layer C is formed. Otherwise, the barrier film and wavelength conversion sheet of Comparative Example 1 are obtained in the same manner as in Example 1.

[0300] [Comparative Examples 2-15]

[0301] The thicknesses of the organic coating layer B and the base coating layer D were changed to the values ​​in Table 2. Otherwise, the barrier films and wavelength conversion sheets of Comparative Examples 2 to 15 were obtained in the same manner as in Example 1.

[0302] In Comparative Examples 12-15, the base coating was formed using the aforementioned base coating forming coating liquid 2. Furthermore, the refractive index n of the base coating in Comparative Examples 12-15... D It is 1.58.

[0303] [Table 1]

[0304]

[0305] [Table 2]

[0306]

[0307] The results in Tables 1 and 2 confirm that the barrier film of the embodiment can suppress hue changes when applied to a wavelength conversion sheet.

[0308] On the other hand, it can be confirmed that the barrier film of the comparative example cannot suppress hue changes when applied to a wavelength conversion film. The barrier film of Comparative Example 1, due to t B For those with a wavelength between 150nm and 500nm and t D / t B The pH value is between 0.55 and 1.65, but it lacks an inorganic oxide layer (C), therefore its barrier properties are poor and it cannot suppress color variations. The barrier films of Comparative Examples 2-15, due to t... B and t D / t B At least one of them is outside the specified range, so the change in hue cannot be suppressed.

[0309] Symbol Explanation

[0310] 10: Translucent substrate

[0311] 21: Inorganic oxide layer A

[0312] 22: Inorganic oxide layer C

[0313] 30: Organic coating layer B

[0314] 40: Primer D

[0315] 50: Quantum dots contain layers

[0316] 100: Barrier membrane

[0317] 100a: Barrier membrane

[0318] 100b: Barrier membrane

[0319] 200: Wavelength conversion plate

[0320] 210: Light source

[0321] 220: Optical plate

[0322] 221: Light guide plate

[0323] 222: Diffuser

[0324] 230: Reflector

[0325] 240: Prism Sheet

[0326] 300: Backlight

[0327] 301: Edge-lit backlight

[0328] 302: Direct-lit backlight

Claims

1. A barrier film for a wavelength conversion sheet, comprising, sequentially on a light-transmitting substrate, an inorganic oxide layer A, an organic coating layer B, an inorganic oxide layer C, and a base coating layer D. The organic coating layer B comprises polyvinyl alcohol. The base coating D comprises a polyurethane-based resin composition. The thicknesses of the light-transmitting substrate, the inorganic oxide layer A, the organic coating layer B, the inorganic oxide layer C, and the base coating layer D are defined as t0, t1, t2, t3, t4, t5, t6, t7, t8, t9, t1 ... A t B t C and t D hour, t B For wavelengths between 150nm and 500nm, and... t D / t B It is between 0.55 and 1.

65.

2. The barrier membrane as described in claim 1, wherein, The inorganic oxide layer A and the inorganic oxide layer C contain aluminum oxide or silicon oxide.

3. The barrier membrane as described in claim 1, wherein, Based on the total amount of the base coating layer D, the content of the polyurethane resin composition is 40% by mass or more.

4. The barrier membrane as described in claim 1, wherein, t D / t B It is 0.55 or higher and 0.93 or lower, or 1.12 or higher and 1.65 or lower.

5. A wavelength conversion sheet having a quantum dot-containing layer comprising quantum dots and a barrier film laminated on both sides of the quantum dot-containing layer, wherein, As the barrier film, the barrier film according to any one of claims 1 to 4 was laminated such that the side opposite to the light-transmitting substrate faces the side containing the quantum dot layer.

6. The wavelength conversion chip as described in claim 5, wherein, The quantum dot contains a layer that is in contact with the undercoat layer D of the barrier films on both sides.

7. A backlight source comprising at least one light source emitting primary light, an optical plate disposed adjacent to the light source for guiding or diffusing light, and a wavelength conversion sheet disposed on the light emitting side of the optical plate, wherein, The wavelength conversion chip is the wavelength conversion chip as described in claim 5.

8. A liquid crystal display device, comprising a backlight and a liquid crystal panel, wherein, The backlight source is the backlight source described in claim 7.

Citation Information

Patent Citations

  • Vapor deposition coating liquid

    JP2001288408A

  • Vapor deposition coating fluid

    JP2003026996A

  • Radiation-sensitive resin composition, cured film, light-emitting element, wavelength conversion film, and method for forming light-emitting layer

    JP2015018131A

  • Barrier film and wavelength conversion sheet using barrier film

    JP2019126924A

  • Barrier film, wavelength conversion sheet, and manufacturing method of wavelength conversion sheet

    JP2020019141A